METTL3-dependent m6A modification programs T follicular helper cell differentiation - Yingpeng Yao (Nature Portfolio, 2021)
T follicular helper (TFH) cells are specialized effector CD4+ T cells that are critical in humoral immunity, but the function of post-transcriptional regulation is not clearly defined. Here, the authors demonstrate that RNA methylation is important for TFH effector differentiation and subsequent antibody formation through stabilization of Tcf7 transcripts.